Understanding The Behavior of Paying Professional Zakat: A Perspective on The Extended Theory of Planned Behavior - Rohmah, Yuli Fajar; Handayani, Wuri (Universitas Muhammadiyah Yogyakarta, 2025)
The main objective of this research is to explore the factors that impact individuals' willingness to pay Zakat on their employment income or professional Zakat based on the Extended Theory of Planned Behavior (ETPB). The research approach employed in this study was quantitative research based on primary data. To gather the necessary data, a survey of civil servants (PNS) was conducted in five departments of the Yogyakarta City government, namely the Health Department, Environmental Department, Tourism Department, Education Department, and Agriculture Department. 145 valid questionnaires were analyzed using the partial least squares structural equation modelling (PLS-SEM). The findings of the research indicate that subjective norms, the credibility of Zakat Institutions, and information from Zakat management institutions positively impact the intention to pay Zakat. Nevertheless, the intention to pay Zakat was not positively influenced by attitude, perceived behavioral control, or understanding of the profession. This study's implications may assist regulators and policymakers in increasing public awareness of Zakat contributions. To achieve this, Zakat institutions could make efforts to improve dissemination, issue circulars, improve services, and promote transparency, particularly in the collection and distribution of Zakat funds